PENGARUH FINANCIAL RISK DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR PROPERTY DAN REALESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA) - admin, Febiwenesya Forever B11111081 (Jurnal Manajemen Update, 2016)
This studyâ€™s purposes are to analyze the effect of financial risk and the implication of Good Corporate Governance (GCG) that can affect the Corporate Value. The Financial Riskâ€™s proxy in this study is Debt to Equity ratio, whereas the GCGâ€™s proxy are institutional ownership, manajerial ownership, audit comittes, and independence commissioners. The Firmâ€™s Value proxy in this study is Tobinâ€™s Q Value. The Data Collection method in this study use purposive sampling on property and real estate Subsector firms those listed in BEI during 2009-2014. 34 firmsare thetotal samples of this research. The analysis method in this study used classic assumption test and multiple regression method to test the validity of the hypothesis. The results of this study show that financial risks proxy (DER) doesnâ€™t have any signicance towards firmâ€™s value. Whereas, some ofÂ  Good Corporate Governance variables are have different significance results among of it. Institutional ownership is not significantly affect towards firmâ€™s value, Managerial ownership is not significantly affect towards firmâ€™s value, and â€œindependent commissionersâ€ variable is not significantly affect towards firmâ€™s value, but â€œthe number of Audit Committeeâ€ variablehas significant affection toward firmâ€™s value. Keywords :Â Â Â Â Â  Firmâ€™s Value (Tobinâ€™s Q), financial risk, debt to equity ratio, good corporate governance, Institutional Ownership, managerial ownership, audit committee, independent commissioners. Â  Â